(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article discusses the concepts of polysemy and homonymy in linguistics, providing definitions and examples of each. It explains how polysemy refers to the phenomenon of a single word having multiple related meanings, and how homonymy refers to the phenomenon of different words that are spelled and pronounced the same but have different meanings. The article also explores the implications of polysemy and homonymy for language understanding and communication. Overall, it offers a comprehensive analysis of these two important linguistic phenomena and their relevance in language processing.